Analisis Otonomi Daerah Berdasarkan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Muhammad Khaidir Kahfi Natsir (International Forum of Researchers and Lecturers, 2025)
This paper discusses in depth the regulation and implementation of Law Number 23 of 2014 on Regional Government in Indonesia, as well as its impact on regional autonomy and the relationship between central and regional governments. This law serves as an essential foundation for more effective and efficient regional government management, but it also presents various challenges in its implementation. The issues raised in this research include challenges in applying the principles of decentralization and deconcentration, as well as the authority granted to regional governments in managing natural resources, public services, and other aspects related to regional autonomy. The aim of this research is to explore and analyze the legal aspects that influence the effectiveness of regional policies, using a normative legal approach and descriptive analysis. This research method involves an in-depth literature study, including an examination of existing regulations and analysis of relevant literature. The research findings indicate that although the Regional Government Law provides rights and authorities for regions to manage their own governmental affairs, there are several obstacles in its implementation. These obstacles include regulatory ambiguities, a lack of harmonization between implementing regulations, and issues in monitoring and evaluating the performance of regional governments. Furthermore, the relationship between central and regional governments often does not function optimally, resulting in uncertainties in carrying out the duties and responsibilities of each party. The conclusions drawn from this research emphasize the need for evaluation and adjustment of existing regulations, as well as the importance of better collaboration between central and regional governments. This is necessary to ensure that the goals of equitable and fair development can be achieved. The research also recommends the need for clearer and more integrated implementing regulations, as well as enhancing human resource capacity at the regional level to support effective policy implementation.